THE ROLE OF INDEPENDENT THINKING IN YOUNG PEOPLE IN THE FORMATION OF INNOVATIVE IDEAS IN SOCIETY - Rakhmanov Abdurauf Mukhammedovich (European Journal of Life Safety and Stability (2660-9630), 2023)
In the process of covering this article, while we are building New Uzbekistan today, we will analyze the attention given to young people in the society, the conditions and opportunities created, the fact that young people have an independent opinion, the importance of promoting innovative ideas in the development of society, and the definitions of the concept of innovation given by local and foreign scientists.